Stability of a combinatorial vector partition problem - Emelichev, V. A.; Gurevskii, E. E. (Cybernetics and systems analysis, 2007)
The vector variant of the partition problem is considered. It is shown that the coincidence of the Pareto and Slater sets is the necessary and sufficient condition of stability of the problem with respect to its functional. [PUBLICATION ABSTRACT]